2011
DOI: 10.1037/a0021402
|View full text |Cite
|
Sign up to set email alerts
|

Emotion deficits in schizophrenia: Timing matters.

Abstract: The past two decades of research on emotional response in schizophrenia has demonstrated that people with schizophrenia do not have a marked deficit in reported emotional experience in the presence of emotionally evocative stimuli. However, the extent to which people with schizophrenia maintain their emotional state to guide future behavior remains a largely unexplored area of investigation. In the present study, we tested hypotheses about whether people with schizophrenia maintained their emotional state in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 58 publications
4
46
0
Order By: Relevance
“…Inappropriate value representation in people with schizophrenia may also compromise their motivation to approach or avoid leading to suboptimal decision-making (Germans and Kring, 2000;Gold et al, 2012;Gold et al, 2008). Finally, the maintenance and recall of emotional experience which are impaired in people with schizophrenia are essential for anticipatory pleasure encoding (Kring et al, 2011;Strauss and Gold, 2012). However, to establish a causal relationship between the dampened anticipatory pleasure and the abovementioned factors in schizophrenia-spectrum disorders requires further research.…”
Section: Deficits In Anticipatory Pleasurementioning
confidence: 92%
“…Inappropriate value representation in people with schizophrenia may also compromise their motivation to approach or avoid leading to suboptimal decision-making (Germans and Kring, 2000;Gold et al, 2012;Gold et al, 2008). Finally, the maintenance and recall of emotional experience which are impaired in people with schizophrenia are essential for anticipatory pleasure encoding (Kring et al, 2011;Strauss and Gold, 2012). However, to establish a causal relationship between the dampened anticipatory pleasure and the abovementioned factors in schizophrenia-spectrum disorders requires further research.…”
Section: Deficits In Anticipatory Pleasurementioning
confidence: 92%
“…Further, individuals with schizophrenia show intact responses in emotion-modulated startle paradigms during the presentation of pleasant stimuli, when given sufficient time to process the stimuli (Schlenker et al 1995;Curtis et al 1999;Volz et al 2003;Kring et al 2011) and intact memory enhancement for positive stimuli (Mathews and Barch 2004;Horan et al 2006;Hall et al 2007) though see (Herbener et al 2007). …”
Section: Schizophreniamentioning
confidence: 95%
“…60 The evidence indicates that people with schizophrenia may have difficulty maintaining an emotional experience over time. 61 Consequently, due to working memory deficits, it should not be surprising that people with schizophrenia have difficulty holding on to prior emotional experiences, leading to blunting of emotional responses. This hypothesis is in accordance with previous work by Burbridge and Barch 62 who found that working memory moderated the relationship between the symptom of anhedonia and self-reported experience of enjoyment of pleasurable stimuli.…”
Section: Discussionmentioning
confidence: 99%